Сравнение условий ведения бизнеса в Чешской Республике и Российской Федерации - Kataev, Egor; Svobodová, Ivana, 1969-; Hartman, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The purpose of my bachelor work is conditions comparison of conducting business activity in the Czech Republic and the Russian Federation. Bachelor work has been divided into two main parts. The first part of work describes basic provisions of laws, processes of registration of the enterprises in both countries, systems of the taxation and accounting. The second part of work provides expert`s estimations and the estimations of real businessmen of the Czech Republic and the Russian Federation.
Vedoucí práce: Ivana Svobodová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomika predprijatija i menedžment [obor bakal. práce]; bakalářské práce; bachelor's theses